Primat der Politik über die Geschichte: Vergangenheit und Gegenwart bei Gramsci und Benjamin / Primacy of Politics over History: Past and Present in Gramsci and Benjamin - Pohn-Lauggas, Ingo (International Gramsci Journal, 2023)
This article compares the philosophies of history of Antonio Gramsci and Walter Benjamin and chooses a specific approach since the topic of “history” is an overarching meta-theme for both thinkers: After a general introduction, the category “Past and Present” developed by Gramsci in the Prison Notebooks is juxtaposed with Benjamin’s “Concept of History”. With one eye on the biographical experience, the “ensemble of the social relations” (Marx) inscribed in the human being is included and related to the historical process and, not least, to questions of historiography. Central clues are the possibility of insight on the one hand and of politics on the other hand; for it turns out that in questions of history, Benjamin becomes political with the aim of insight, while Gramsci addresses questions of insight with the aim of political action.